Domestic PV System with Feedback Linearization-based Control Strategy for Module-level MPPT under Partial Shading Condition - Hamidreza Toodeji (IEEE, 2021)
A partial shading condition can adversely affect the energy conversion efficiency of domestic photovoltaic (PV) systems. Connecting each PV module to a microinverter and performing module-level maximum power point tracking (MPPT) are proposed as promising solutions. In this paper, a feedback linearization-based control strategy is designed for the nonlinear system by a novel straightforward approach. The obtained nonlinear control law can independently govern each microin-verter, providing module-level MPPT for PV modules without DC optimizer. Moreover, PV modules can be easily connected or disconnected due to the lug-and-play ability of the proposed controller. As a result, the proposed PV system can be easily maintained and extended even by non-expert users. Moreover, any module failure in the proposed PV system can be tolerated without impacts on the normal operation of other PV modules. The advantages of the proposed control strategy are verified by the simulation of a test PV system in MATLAB/Simulink under various partial shading conditions as well as adding or removing PV modules.